MECHANICAL-ACOUSTIC SYSTEM EQUIVALENT OF SEISMIC-WAVE GENERATOR WITH MULTIFIER - Vladimir P. Pevchev; Andrey K. Kudinov (Advanced Engineering Research, 2011)
The application of methods of the electro-acoustic and electro-mechanical analogies to simulate a seismic-wave generator with hydraulic multiplier by the electric circuit is analyzed. An original algorithm of integrating the electric circuit equivalent of mechanical and acoustic subsystems of the mechanical-acoustic system is offered.